Morphological, molecular, and biological characterization of bulb rot pathogens in stored Lanzhou lily and the in vitro antifungal efficacy of three plant essential oils - Liu, Chaoqun; Wang, Yinquan; Jin, Ling; Wang, Yan; Liu, Dongling (Frontiers in Microbiology, 2024)
Lanzhou lily (Lilium davidii var. willmottiae) is an exclusive sweet lily variety indigenous to China, which is susceptible to bulbous rot caused by fungal infection during storage. The pathogenicity of the pure culture isolated from diseased tissue was confirmed in accordance with Koch's postulates, and the pathomycetes were identified based on their morphological and molecular characteristics. Furthermore, the biological characteristics of the pathogens were investigated, followed by evaluation of antifungal effects of three plant essential oils against them. Two strains of fungi were isolated from Lanzhou lily rot, which were identified as Fusarium oxysporum Schl. and Aspergillus sydowii (Bain. Et sart.) Thom et church, at the same time, the pathogenicity of these two strains of fungi was identified. The results demonstrated that only F. oxysporum induced rot with similar symptoms during the post-harvest storage period. So we carryied out a study on the biological characteristics of F. oxysporum. Based on the biological characteristics of F. oxysporum, potato maltose agar and lily dextrose agar were identified as the most suitable media. Sucrose was determined to be the optimal carbon source, while ammonium nitrate authenticated the best nitrogen source. The mycelium growth and sporulation exhibited an optimum pH value of 6. Total darkness facilitated mycelial growth and conidial germination. The ideal temperature for growth was found to be 28℃, while relative humidity did not significantly impact mycelial growth; however, a relative humidity of 55% was most favorable for spore production. Amongst the three essential oils tested, cinnamon essential oil displayed superior antifungal efficacy against F. oxysporum, whereas angelica essential oil and tea tree essential oil also exhibited certain inhibitory effects on this pathogen. This research provides valuable theoretical insights for disease control during the storage and transportation of Lanzhou lily.